2019
DOI: 10.1111/ijn.12796
|View full text |Cite
|
Sign up to set email alerts
|

Stress, anxiety and depression perceived by couples with recurrent miscarriage

Abstract: Aim Recurrent miscarriage is considered a major life event. The main purposes of this study were to compare the differences in stress, anxiety, social support, sleep quality and depressive symptoms in couples experiencing recurrent miscarriage compared to peers who experience full‐term normal childbirth in southern Taiwan. Methods Convenience sampling and snowball sampling were used respectively to recruit 78 couples with and 80 couples without recurrent miscarriage from October 2014 to July 2015. Five structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…We found that childless women had higher anxiety levels than those who had one or more children during the pregnancy period. The Chinese people consider fertility and childbearing ability to be of great importance for women; pregnancy and childbirth are essential for women and family integrity (Chen et al, 2020;Fu et al, 2015). Age, duration of the marriage and the number of previous miscarriages were negatively correlated with depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that childless women had higher anxiety levels than those who had one or more children during the pregnancy period. The Chinese people consider fertility and childbearing ability to be of great importance for women; pregnancy and childbirth are essential for women and family integrity (Chen et al, 2020;Fu et al, 2015). Age, duration of the marriage and the number of previous miscarriages were negatively correlated with depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…RM affects 5% of couples worldwide who seek to have children, which is an essential reproductive health issue (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary medical knowledge confirms that infertility may also have a psychogenic basis (Wass, Stewart, 2011). Many authors indicate that infertility and miscarriage are phenomena burdened with severe stress (Rooney, Domar, 2018, Boivin, & Lancastle, 2010, which not only reduces the life satisfaction of infertile spouses (Galhardo et al, 2020) and after miscarriage ( Tavoli et al, 2018), but is also associated with poorer effects of infertility treatment (Rooney & Domar, 2018) and is a significant risk factor for miscarriage (Chen et al, 2019, Qu et al, 2017. Therefore, there is a great need for professional psychological help offered to infertile couples and after experiencing a miscarriage, according to individual needs, using modern techniques of modern medicine (Greil et al, 2010, Lafarge, Kathryn Mitchell, Fox, 2017.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Research on mental health subsequent to early pregnancy loss as a result of elective induced abortions has historically been polarized, but recent research indicates an increased correlation to the genesis or exacerbation of substance abuse and affective disorders including suicidal ideation ( Broen et al, 2005 ; Coleman, 2011 ; Steinberg and Finer, 2011 ; Bellieni and Buonocore, 2013 ; Sullins, 2016 , 2019 ; Reardon, 2018 ). Several recent international studies have demonstrated that repetitive early pregnancy loss, including both miscarriage and induced abortions, is associated with increased levels of distress, depression, anxiety, and reduced quality of life scores in social and mental health categories ( Kolte et al, 2015 ; Tavoli et al, 2018 ; Chen et al, 2020 ; Gao et al, 2020 ). Prolonged grief reactions related to other types of loss (spouse or older children) have been associated with poor mental and physical health outcomes including substance misuse, affective disorders, social and functional impairments, accidents, hypertension, cardiovascular disease, stroke, cancer, and suicidal ideation ( Prigerson et al, 1997 ; Gerra et al, 2003 ; Hart et al, 2007 ; Lannen et al, 2008 ; Jones et al, 2010 ; Buckley et al, 2012 ; Nielsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%